Difusi Inovasi Layanan Identitas Kependudukan Digital di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Cirebon - Miftahurrizqi Miftahurrizqi Miftahurrizqi; Lina Aryani; Lolita Deby Mahendra Putri (Jurnal Ilmiah Wahana Pendidikan, 2026)
The implementation of Digital Population Identity (IKD) in Cirebon Regency is stagnating, with 2025 realization reaching only 5.40% of the national target. This study aims to analyze the dynamics of IKD diffusion and map the inhibiting factors using Rogers' (2003) Diffusion of Innovations theory. The research method used is descriptive qualitative with data collection through observation and in-depth interviews, utilizing purposive sampling. The results reveal barriers across four dimensions. In innovation characteristics, IKD fails to become a primary need, viewed merely as a backup instrument due to public ecosystem unreadiness and procedural complexity. Communication channels suffer from inequality where face-to-face socialization is minimal, failing to reach the grassroots level. The time dimension shows behavioral anomalies: the younger generation tends to be critically slow, while the older generation is instant but passive. Finally, the social system experiences functional fragmentation due to reactive-conditional change agent strategies and the failure of formal village leaders' roles. The study concludes that the main barriers lie in social inertia and a data security trust crisis, necessitating a service transformation into proactive-scheduled approaches and mandatory ecosystem regulations.